Pengaruh Firm Size, Subsidiaries, dan Auditor Size terhadap Audit Fee - Nurdjanti, Fisca Adhitya; Pramesti, Wahyu (JIFA (Journal of Islamic Finance and Accounting), 2018)
The aims of this study is to determine the effect of firm size, subsidiaries, and auditor size to the audit fee. This study tested the company listed in Indonesia Sharia Stock Index (ISSI) for the year 2013-2016. This study obtained 37 companies as a sample in four years. Data were analyzed using multiple linear regression analysis model. The results of this study showed that firm size, subsidiaries, and auditor size have positive and significant impact on audit fees. In this study the entire hypothesis can be accepted.